Carbon quantum dot modified zinc oxide gas sensor and preparation method thereof
By coating carbon quantum dots on the zinc oxide nanowire array and adopting glass through-hole packaging technology, the existing gas sensors have insufficient accuracy and high working temperature in complex gas environments, and the gas detection effect with high sensitivity and low temperature is achieved.
Patent Information
- Application Number
- CN202411713029.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
When existing metal oxide gas sensors detect complex and low-concentration polluted gases, their accuracy is difficult to meet the needs and their operating temperature is high.
The zinc oxide gas sensor is modified with carbon quantum dots, and the gas contact area and adsorption capacity are improved by coating carbon quantum dots on the zinc oxide nanowire array list surface and integrating it in glass through-hole packaging technology.
It significantly improves the gas response and selectivity of the sensor, reduces the operating temperature, and improves the high sensitivity detection capability of acetone gas.
Smart Images

Figure CN119534560A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a carbon quantum dot modified zinc oxide gas sensor and a preparation method thereof. Background Art
[0002] With the rapid development of industrialization and urbanization, people's living standards are constantly improving, but environmental problems are becoming more and more serious. For example: acetone, formaldehyde, ammonia, etc. Harmful gases not only damage the environment, but also affect human health. The key to solving these problems is to be able to quickly and accurately detect polluted gases, but in relatively harsh environments, when the measured gas composition is complex and the concentration is low, the accuracy of conventional testing methods is difficult to meet the needs of users. Therefore, it is of great significance to explore and develop a metal oxide gas sensor with excellent performance.
[0003] At present, gas sensors based on metal oxide architectures, such as ZnO, SnO2 and WO3, have occupied an important position in the field of gas detection due to their low cost, low power consumption, excellent sensitivity, and fast response and recovery time. Among them, ZnO, as a crucial direct bandgap n-type semiconductor material, has a wide bandgap of up to 3.37eV and an excellent exciton binding energy of 60MeV, which lays a solid foundation for its application in the field of electronics. ZnO also exhibits a variety of nanostructure morphologies, including nanotubes, nanorods, nanosheets, nanospheres and nanofibers. These unique structures give ZnO more abundant physical and chemical properties. It is particularly worth mentioning that the one-dimensional ZnO nanostructure grown on a polished silicon substrate has opened up a new path for improving the sensitivity of gas sensors due to its extremely high surface-to-volume ratio. ZnO nanostructures have attracted much attention in the field of gas sensor research due to their significant advantages such as high surface-to-volume ratio and high stability. However, pure ZnO materials still have certain limitations in terms of selectivity, sensitivity and operating temperature. To this end, researchers have conducted in-depth modification research on ZnO materials through advanced methods such as doping, surface modification and construction of heterostructures, in order to significantly improve its gas-sensing performance and further broaden the application of ZnO in the field of gas sensors.
[0004] Carbon dots (CDs) are a new type of carbon nanomaterial, usually quasi-spherical nanoparticles with a size of less than 10nm. The center is usually a carbon core with crystalline sp2 or non-crystalline sp3 hybridization, and the surface is composed of a variety of active functional groups, including epoxy, carbonyl, carboxyl and hydroxyl groups. The high surface-to-volume ratio and rich surface functional groups of carbon dots can promote the adsorption of target gases. The specific functional groups on the surface of carbon dots are expected to improve the selectivity of target gases and reduce the operating temperature. Unlike most gas sensors based on metal oxides, since carbon dots have semiconductor properties at room temperature, gas sensors based on nanoscale carbon dots are likely to operate at room temperature rather than high temperature.
[0005] Therefore, it is of great significance to study a carbon quantum dot-modified zinc oxide gas sensor based on glass through-hole packaging technology to improve sensitivity and selectivity and reduce operating temperature. Summary of the invention
[0006] The purpose of the present invention is to provide a carbon quantum dot modified zinc oxide gas sensor and a preparation method thereof in order to overcome the deficiencies of the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a carbon quantum dot modified zinc oxide gas sensor, which comprises a substrate with a folded structure, a gas sensitive unit, and a packaging cavity;
[0009] The gas sensing unit comprises a zinc oxide nanowire array and carbon quantum dots modified on the surface of the zinc oxide nanowire array.
[0010] Preferably, the substrate with the corrugated structure comprises a silicon substrate at the bottom, a columnar structure and an insulating layer at the surface, and the gas sensing unit is grown on the surface of the substrate with the corrugated structure.
[0011] Preferably, the columnar structure is cylindrical, the diameter d of the columnar structure is 10 μm≤d≤50 μm, the height h is 10 μm≤h≤100 μm, and the gap L between the cylinders is 20 μm≤L≤50 μm.
[0012] Preferably, the diameter d of the carbon quantum dots is 5 nm≤d≤50 nm.
[0013] Preferably, the packaging cavity comprises a bottom electrode, a glass cavity, a through-hole electrode and a top test electrode; the through-hole electrodes are arranged at two ends of the glass cavity, and the through-hole electrodes connect the bottom electrode and the top test electrode.
[0014] The present invention also provides a method for preparing the carbon quantum dot modified zinc oxide gas sensor, comprising the following steps:
[0015] 1) Photolithography and etching are performed sequentially on the surface of a silicon substrate to obtain a substrate with a columnar fold structure;
[0016] 2) depositing an insulating layer on the surface of the substrate with the columnar fold structure, and preparing bottom electrodes at both ends of the insulating layer;
[0017] 3) Spin coating a seed layer on the surface of the insulating layer, and growing a zinc oxide nanowire array on a silicon substrate containing the seed layer in a growth solution;
[0018] 4) coating carbon quantum dots on the surface of zinc oxide nanowire arrays;
[0019] 5) Use glass through-hole technology for packaging and reserve a gas channel; lead out the top test electrode through the glass through-hole, and the through-hole electrode connects the bottom electrode and the top test electrode.
[0020] Preferably, photolithography is performed after spin coating photoresist on the surface of the silicon substrate, the rotation speed of the spin coating photoresist is 2500-3500 r / min, and the time is 1.5-2.5 min;
[0021] During the photolithography process, pre-baking: 62-68°C, 2.5-3.5 min; 90-100°C, 5.5-6.5 min; exposure 105-115 s; post-baking: 62-68°C, 0.8-1.2 min; 90-100°C, 4.5-5.5 min; development 45-55 s.
[0022] Preferably, the insulating layer is a silicon dioxide insulating layer; separate bottom electrodes are prepared at both ends of the insulating layer by magnetron sputtering coating, and the bottom electrodes are gold electrodes; the thickness of each bottom electrode is 85 to 95 nm.
[0023] Preferably, the raw materials of the seed layer are zinc acetate, ethanolamine and anhydrous ethanol, and the molar ratio of zinc acetate to ethanolamine is 1-2:1-2;
[0024] The process of spin coating the seed layer is first spin coating, second spin coating, and heating. The rotation speed of the first spin coating is 970-1030 r / min, the time is 8-12 s, the rotation speed of the second spin coating is 1500-2500 r / min, the time is 25-35 s; the heating temperature is 280-320°C, and the time is 22-27 min.
[0025] Preferably, the raw materials of the growth solution are zinc nitrate, hexamethylenetetramine and water, and the molar ratio of zinc nitrate to hexamethylenetetramine is 1-1.5:1-1.5; the temperature for growing the zinc oxide nanowire array is 90-98°C, and the time is 5.5-6.5h.
[0026] The beneficial effects of the present invention include the following:
[0027] 1) The present invention constructs a precise wrinkled micro-nano structure on the surface of the silicon wafer, and uses it as a substrate to cleverly integrate zinc oxide nanowires modified with carbon quantum dots. Through an efficient spin coating process, the seamless integration of nanoscale, nearly spherical carbon dot solutions and other high-performance gas-sensitive materials is achieved. This innovative strategy significantly improves the gas response capability of the sensor. Subsequently, the through-glass via packaging technology (TGV) is used to prepare a three-dimensional integrated carbon quantum dot-modified zinc oxide gas sensor, which exhibits excellent gas sensitivity.
[0028] 2) In the carbon quantum dot-modified zinc oxide gas sensor of the present invention, after the gas is introduced into the cavity, the gas sensitive unit grown on the surface of the substrate with a pleated structure can increase the gas contact area, and the gas adsorption effect is enhanced by modifying the carbon quantum dots on the surface of the zinc oxide nanowire array, thereby achieving the purpose of improving sensitivity and selectivity and reducing detection temperature. It can be used for high-sensitivity acetone gas detection.
[0029] 3) The preparation method of the present invention is not only simple and fast, but also has multiple advantages such as low toxicity, significant cost-effectiveness, excellent biocompatibility and environmental friendliness, paving a solid road for the widespread application of carbon dot-based gas sensors. The unique structural design of the gas sensor of the present invention has shown extremely broad application prospects and far-reaching value in promoting the miniaturization process of gas sensors and achieving high performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A process diagram for preparing the carbon quantum dot modified zinc oxide gas sensor of the present invention;
[0031] Figure 2 Schematic diagram of the structure of the carbon quantum dot modified zinc oxide gas sensor of the present invention, wherein 10 is a silicon substrate, 11 is a wrinkled structure, 111 is a columnar structure, 112 is an insulating layer, 12 is a gas sensitive unit, 121 is a zinc oxide nanowire, 122 is a carbon quantum dot, 20 is a bottom electrode, 21 is a through-hole electrode, 22 is a top test electrode, and 30 is a packaging chamber;
[0032] Figure 3 The SEM image of the surface columnar structure of Example 2, wherein a is before removing the photoresist, and b is after removing the photoresist;
[0033] Figure 4 This is a SEM image of the zinc oxide nanowire array grown on the surface of the wrinkled substrate of Example 2;
[0034] Figure 5 This is a TEM image of carbon quantum dots coated on the surface of the zinc oxide nanowire array of Example 1;
[0035] Figure 6The sensitivity curves of Comparative Example 1 and Comparative Example 2 in a 400ppm acetone environment at different temperatures;
[0036] Figure 7 The sensitivity curves of Example 1 and Comparative Example 3 in a 400 ppm acetone environment at different temperatures;
[0037] Figure 8 The selectivity of Comparative Example 1 and Comparative Example 2 to different gases at 300°C. DETAILED DESCRIPTION
[0038] The present invention provides a carbon quantum dot modified zinc oxide gas sensor, which comprises a substrate with a folded structure, a gas sensitive unit, and a packaging cavity;
[0039] The gas sensing unit comprises a zinc oxide nanowire array and carbon quantum dots modified on the surface of the zinc oxide nanowire array.
[0040] In the present invention, the substrate with a corrugated structure preferably comprises a silicon substrate at the bottom, a columnar structure on the surface and an insulating layer, and the gas sensing unit is preferably grown on the surface of the substrate with a corrugated structure.
[0041] In the present invention, the columnar structure is preferably cylindrical, the diameter d of the columnar structure is preferably 10μm≤d≤50μm, more preferably 20μm≤d≤40μm, more preferably 25μm≤d≤35μm, the height h is preferably 10μm≤h≤100μm, more preferably 30μm≤h≤80μm, more preferably 40μm≤h≤70μm, and the gap L between the cylinders is preferably 20μm≤L≤50μm, more preferably 25μm≤L≤45μm, more preferably 30μm≤L≤40μm.
[0042] In the present invention, the columnar structure is cylindrical, which can effectively increase the contact area between the gas and the gas sensitive material, thereby improving the gas sensitive characteristics of the sensor.
[0043] In the present invention, the diameter d of the carbon quantum dots is preferably 5 nm ≤ d ≤ 50 nm, more preferably 10 nm ≤ d ≤ 40 nm, and even more preferably 20 nm ≤ d ≤ 30 nm.
[0044] In the present invention, carbon quantum dots can effectively increase the reaction area between gas and gas-sensitive materials, thereby improving the gas-sensitive properties of the sensor.
[0045] In the present invention, the packaging cavity preferably includes a bottom electrode, a glass cavity, a through-hole electrode and a top test electrode; the through-hole electrodes are preferably arranged at both ends of the glass cavity, and the through-hole electrodes connect the bottom electrode and the top test electrode.
[0046] In the present invention, the bottom electrode is used for signal testing.
[0047] The present invention also provides a method for preparing the carbon quantum dot modified zinc oxide gas sensor, comprising the following steps:
[0048] 1) Photolithography and etching are performed sequentially on the surface of a silicon substrate to obtain a substrate with a columnar fold structure;
[0049] 2) depositing an insulating layer on the surface of the substrate with the columnar fold structure, and preparing bottom electrodes at both ends of the insulating layer;
[0050] 3) Spin coating a seed layer on the surface of the insulating layer, and growing a zinc oxide nanowire array on a silicon substrate containing the seed layer in a growth solution;
[0051] 4) coating carbon quantum dots on the surface of zinc oxide nanowire arrays;
[0052] 5) Use glass through-hole technology for packaging and reserve a gas channel; lead out the top test electrode through the glass through-hole, and the through-hole electrode connects the bottom electrode and the top test electrode.
[0053] In the present invention, the silicon substrate is a single-side polished silicon wafer, and the silicon substrate is ultrasonically cleaned with alcohol, acetone and deionized water respectively to remove impurities on the surface of the silicon substrate; the time for ultrasonic cleaning with alcohol, acetone and deionized water is independently preferably 0.5h.
[0054] In the present invention, photolithography is performed after spin coating the photoresist on the surface of the silicon substrate, the rotation speed of the spin coating photoresist is preferably 2500-3500 r / min, more preferably 2800-3200 r / min, more preferably 3000 r / min, the time is preferably 1.5-2.5 min, more preferably 1.8-2.2 min, more preferably 2 min;
[0055] During the photolithography process, the pre-bake is preferably at 62-68°C, 2.5-3.5 min; 90-100°C, 5.5-6.5 min, more preferably 65°C, 3 min; 95°C, 6 min; the exposure is preferably 105-115 s, more preferably 110 s; the post-bake is preferably at 62-68°C, 0.8-1.2 min; 90-100°C, 4.5-5.5 min, more preferably 65°C, 1 min; 95°C, 5 min; the development is preferably 45-55 s, more preferably 50 s.
[0056] In the present invention, the surface columnar structure is prepared by deep silicon etching after photolithography.
[0057] In the present invention, the etching preferably adopts a standard Bosch deep silicon etching process, with SF6 etching for 8 seconds and C4F8 protection for 5 seconds as a complete cycle, and columnar structures of different depths are etched through different numbers of cycles.
[0058] In the present invention, the insulating layer is preferably a silicon dioxide insulating layer; separate bottom electrodes are prepared at both ends of the insulating layer by magnetron sputtering coating, and the bottom electrodes are preferably gold electrodes; the thickness of each bottom electrode is preferably 85 to 95 nm, further preferably 88 to 92 nm, and more preferably 90 nm.
[0059] In the present invention, a silicon dioxide insulating layer is deposited on the silicon substrate to ensure the insulation between the silicon substrate and the gas sensitive material; the silicon dioxide insulating layer and the columnar structure deposited on the surface of the silicon substrate together constitute the fold structure on the surface of the substrate.
[0060] In the present invention, the raw materials of the seed layer are preferably zinc acetate, ethanolamine and anhydrous ethanol, and the molar ratio of zinc acetate to ethanolamine is preferably 1-2:1-2, and more preferably 1:1;
[0061] The process of spin coating the seed layer is first spin coating, second spin coating, and heating. The rotation speed of the first spin coating is preferably 970-1030r / min, more preferably 1000r / min, and the time is preferably 8-12s, more preferably 10s. The rotation speed of the second spin coating is preferably 1500-2500r / min, more preferably 1800-2200r / min, more preferably 2000r / min, and the time is preferably 25-35s, more preferably 27-33s, more preferably 30s; the heating temperature is preferably 280-320℃, more preferably 290-310℃, more preferably 300℃, and the time is preferably 22-27min, more preferably 24-26min, more preferably 25min.
[0062] In the present invention, the raw materials of the growth solution are preferably zinc nitrate, hexamethylenetetramine and water, and the molar ratio of zinc nitrate to hexamethylenetetramine is preferably 1-1.5:1-1.5, more preferably 1-1.2:1-1.2, and more preferably 1:1;
[0063] The temperature for growing the zinc oxide nanowire array is preferably 90 to 98° C., more preferably 93 to 97° C., and more preferably 95° C., and the time is preferably 5.5 to 6.5 h, and more preferably 6 h.
[0064] In the present invention, the silicon substrate containing the seed layer is preferably tilted downward at 45° and placed in a growth solution, and a zinc oxide nanowire array is grown by a hydrothermal method; after the growth is completed, it is rinsed and dried in sequence, the rinsing reagent is preferably water, and the drying temperature is preferably 58-62°C, and more preferably 60°C.
[0065] The process steps for preparing the carbon quantum dot modified zinc oxide gas sensor of the present invention are as follows: Figure 1 As shown; the structural schematic diagram of the carbon quantum dot modified zinc oxide gas sensor of the present invention is as shown Figure 2 As shown, 10 is a silicon substrate, 11 is a wrinkled structure, 111 is a columnar structure, 112 is an insulating layer, 12 is a gas sensitive unit, 121 is a zinc oxide nanowire, 122 is a carbon quantum dot, 20 is a bottom electrode, 21 is a through-hole electrode, 22 is a top test electrode, and 30 is a packaging chamber.
[0066] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0067] Example 1
[0068] The three-dimensional integrated carbon quantum dot modified zinc oxide gas sensor includes a substrate with a pleated structure, a gas sensitive unit, and a packaging cavity; the gas sensitive unit includes a zinc oxide nanowire array and carbon quantum dots modified on the surface of the zinc oxide nanowire array; the substrate with a pleated structure is composed of a silicon substrate at the bottom, a columnar structure on the surface, and an insulating layer, and the gas sensitive unit is grown on the surface of the substrate with the pleated structure.
[0069] The preparation method of the carbon quantum dot modified zinc oxide gas sensor comprises the following steps:
[0070] The single-sided polished silicon wafer was ultrasonically cleaned with alcohol, acetone and deionized water respectively. The alcohol, acetone and deionized water were cleaned for 0.5h respectively. The frequency of ultrasonic cleaning was 1MHz to remove impurities on the surface of the silicon substrate. SU-8 photoresist was spin-coated on the surface of the silicon substrate. The speed of the spin-coating photoresist was 3000r / min and the time was 2min. After spin coating, photolithography was performed. The photolithography process was as follows: pre-baking: 65℃, 3min; 95℃, 6min; exposure 110s; post-baking: 65℃, 1min; 95℃, 5min; development 50s. After the photolithography was completed, a circular pattern was displayed on the silicon substrate. After that, the surface columnar structure was prepared by deep silicon etching, and the remaining photoresist on the silicon substrate was stripped with acetone. The diameter of the columnar structure was 15μm, the height was 8μm, and the gap between the cylinders was 20μm.
[0071] The silicon dioxide insulating layer (the thickness of the insulating layer is 1 μm) is deposited on the surface of the columnar silicon substrate by plasma deposition. The silicon dioxide insulating layer and the columnar structure together form the fold structure on the substrate surface. The film is deposited by magnetron sputtering. The process parameters of magnetron sputtering are: the vacuum degree of the process chamber is 5.8×e -5Pa, the plating pot can rotate continuously, the rotation rate is 10r / min, the distance between the target and the substrate is 60cm, and two separated gold bottom electrodes are prepared at both ends of the insulating layer. The thickness of the transition layer Cr is 10nm, and the thickness of each bottom electrode is 90nm.
[0072] The seed layer was spin-coated on the surface of the insulating layer. The silicon substrate containing the seed layer was hydrothermally grown with zinc oxide nanowire arrays in the growth solution, and RTP was used for annealing at a temperature of 300°C for 120 seconds to form an ohmic contact between zinc oxide and the bottom electrode. The specific process is as follows: zinc acetate and ethanolamine were dissolved in anhydrous ethanol at a molar ratio of 1:1 (the concentrations of zinc acetate and ethanolamine in the solution were both 0.05 mol / L), and stirred at 800 r / min for 1 hour in a 60°C water bath with a magnetic stirrer to form a uniform and stable solution. The seed layer was prepared on the insulating layer of the substrate etched with a wrinkled structure by spin coating. The spin coater was first rotated at 1000 r / min for 10 seconds, then at 2000 r / min for 30 seconds, and then the silicon substrate coated with the seed layer was heated to 300°C on a heating table, and heated for 25 minutes to thermally decompose and form ZnO grains. The silicon substrate containing the seed layer was tilted downward at 45° and placed in a growth solution (zinc nitrate and hexamethylenetetramine were added to deionized water at a molar ratio of 1:1, and the concentrations of zinc nitrate and hexamethylenetetramine were both 0.05 mol / L), and grown in a 95°C water bath for 6 hours. The silicon substrate was removed, rinsed with deionized water, and dried on a heating table at 60°C to obtain a zinc oxide nanowire array with an average diameter of 100 nm and a height of 1.6 μm.
[0073] Carbon quantum dots are coated on the surface of zinc oxide nanowire arrays to form gas sensitive units. The diameter of the carbon quantum dots is 10nm.
[0074] The device is packaged in a glass cavity using through-glass via technology, and a gas channel is reserved; the top test electrode is led out through the through-glass via; the packaging cavity is composed of a bottom electrode, a glass cavity, a through-hole electrode and a top test electrode; the through-hole electrodes are arranged at both ends of the glass cavity, and the through-hole electrodes connect the bottom electrode and the top test electrode.
[0075] Example 2
[0076] In the spin coating of the seed layer and the growth of the zinc oxide nanowire array, the spin coater first rotated at 970 r / min for 12 s, then at 1800 r / min for 33 s, and then the silicon substrate coated with the seed layer was heated to 290 ° C on the heating table, and heated for 27 min to thermally decompose and form ZnO grains. The silicon substrate containing the seed layer was tilted downward at 45° and placed in the growth solution (zinc nitrate and hexamethylenetetramine were added to deionized water at a molar ratio of 1:1), and grown in a water bath at 93 ° C for 6.5 h. The diameter of the columnar structure is 20 μm, the height is 16 μm, and the gap between the cylinders is 20 μm.
[0077] Example 3
[0078] In the spin coating of the seed layer and the growth of the zinc oxide nanowire array, the spin coater first rotates at 1030r / min for 8s, then at 2200r / min for 27s, and then the silicon substrate coated with the seed layer is heated to 310°C on a heating table, and heated for 22min for thermal decomposition to form ZnO grains. The silicon substrate containing the seed layer is tilted downward 45° into the growth solution (zinc nitrate and hexamethylenetetramine are added to deionized water at a molar ratio of 1:1.2), and grown in a water bath at 97°C for 5.5h. The diameter of the carbon quantum dot is 30nm. The diameter of the columnar structure is 40μm, the height is 70μm, and the gap between the cylinders is 40μm.
[0079] Comparative Example 1
[0080] The coating of carbon quantum dots in Example 1 was omitted, and the other preparation steps were the same as those in Example 1. The diameter of the columnar structure was 20 μm, the height was 8 μm, and the gap between the columns was 20 μm.
[0081] Comparative Example 2
[0082] The spin coating of photoresist on the silicon substrate, photolithography, etching, and deposition of a silicon dioxide insulating layer in Example 1 are omitted, a silicon substrate without a wrinkled surface structure is used, and the coating of carbon quantum dots is omitted. The other preparation steps are the same as in Example 1.
[0083] Comparative Example 3
[0084] The coating of carbon quantum dots in Example 1 was omitted, and other preparation steps were the same as those in Example 1.
[0085] The SEM image of the surface columnar structure of Example 2 is as follows Figure 3 As shown in the figure, a is before removing the photoresist, and b is after removing the photoresist. From a and b, we can see that the surface of the etched cylinder is flat and smooth, and there is still unetched photoresist on the top of the cylinder; after stripping the remaining photoresist on the silicon substrate with acetone, the cylinder array is neatly arranged, of uniform size, with a smooth surface and no sharp burrs.
[0086] The SEM image of the zinc oxide nanowire array grown on the wrinkled substrate surface of Example 2 is as follows: Figure 4 As shown in the figure, it can be seen that there are zinc oxide nanowires on the top, sidewalls and gaps between the cylinders, which effectively increases the gas contact area, and the zinc oxide nanowires are of uniform size and evenly distributed.
[0087] The TEM image of the carbon quantum dots coated on the surface of the zinc oxide nanowire array of Example 1 is as follows: Figure 5 shown.
[0088] The sensitivity test of the gas sensors prepared in Example 1 and Comparative Examples 1 to 3 was performed. The sensitivity of the resistance change of the gas sensor when exposed to the target gas is defined as:
[0089]
[0090] In formula 1, R air is the resistance in air, R gas To test the resistance in gas.
[0091] (1) Optimal operating temperature of ZnO nanowires
[0092] Under the condition of acetone concentration of 400ppm, the sensitivity at different temperatures was tested. The sensitivity curves of Comparative Example 1 and Comparative Example 2 in 400ppm acetone environment and different temperatures are as follows: Figure 6 As shown. It can be seen from the test results of Comparative Example 1 and Comparative Example 2 that under the test conditions of the same acetone concentration, the optimal operating temperature of the two structure gas sensors is 300°C. However, Comparative Example 1 with a pleated structure has a higher sensitivity. This proves that the pleated structure can effectively improve the sensitivity.
[0093] (2) Optimal working temperature of carbon quantum dots modified zinc oxide materials
[0094] Under the condition of 400ppm acetone concentration, the sensitivity of the carbon quantum dot modified zinc oxide material at different temperatures was tested. The sensitivity curves of Example 1 and Comparative Example 3 in 400ppm acetone environment and different temperatures are as follows: Figure 7 As shown in the figure, when the acetone gas concentration is 400ppm, the optimal operating temperature of the carbon quantum dot modified zinc oxide gas sensor is 100°C, which is significantly lower than that of the comparative example 3 of the pure zinc oxide gas sensor. In addition, at 100°C, the sensitivity of Example 1 is much higher than that of the comparative example 3, indicating that the gas-sensing performance of the gas sensor can be improved by surface modification of carbon quantum dots, and the detection sensitivity can be improved while lowering the operating temperature.
[0095] (3) Different gas selectivity
[0096] Under the optimal working temperature of 300°C, the sensitivity of acetone, ethanol, ammonia, isopropanol, and methanol gases (each gas is 400ppm) was tested. The selectivity of Comparative Example 1 and Comparative Example 2 for different gases at 300°C is as follows: Figure 8 As shown in the figure, the gas sensor has a high sensitivity to acetone and a low sensitivity to other gases, which reflects the good selectivity of the sensor to acetone gas.
[0097] The selectivity test results of Comparative Example 1 and Comparative Example 2 show that the gas sensors of the two structures are most sensitive to acetone gas, and the sensitivity to other gases is not obvious. The above results show that the performance of acetone gas detection is greatly improved by the pleated structure and carbon quantum dots. The sensor can be used for high-sensitivity acetone gas detection, while reducing the detection temperature and improving the sensitivity and selectivity.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A carbon quantum dot modified zinc oxide gas sensor, characterized in that: The carbon quantum dot modified zinc oxide gas sensor comprises a substrate with a folded structure, a gas sensitive unit, and a packaging cavity; The gas sensing unit comprises a zinc oxide nanowire array and carbon quantum dots modified on the surface of the zinc oxide nanowire array.
2. The carbon quantum dot modified zinc oxide gas sensor according to claim 1, characterized in that: The substrate with the corrugated structure comprises a silicon substrate at the bottom, a columnar structure and an insulating layer at the surface, and a gas sensing unit is grown on the surface of the substrate with the corrugated structure.
3. The carbon quantum dot modified zinc oxide gas sensor according to claim 2, characterized in that: The columnar structure is cylindrical, the diameter d of the columnar structure is 10 μm≤d≤50 μm, the height h is 10 μm≤h≤100 μm, and the gap L between the cylinders is 20 μm≤L≤50 μm.
4. The carbon quantum dot modified zinc oxide gas sensor according to claim 1 or 3, characterized in that: The diameter d of the carbon quantum dots is 5nm≤d≤50nm.
5. The carbon quantum dot modified zinc oxide gas sensor according to claim 4, characterized in that: The packaging cavity comprises a bottom electrode, a glass cavity, a through-hole electrode and a top test electrode; the through-hole electrodes are arranged at two ends of the glass cavity, and the through-hole electrodes connect the bottom electrode and the top test electrode.
6. The method for preparing a carbon quantum dot modified zinc oxide gas sensor according to any one of claims 1 to 5, characterized in that: The following steps are included: 1) Photolithography and etching are sequentially performed on the surface of a silicon substrate to obtain a substrate with a columnar fold structure; 2) depositing an insulating layer on the surface of the substrate with the columnar fold structure, and preparing bottom electrodes at both ends of the insulating layer; 3) Spin coating a seed layer on the surface of the insulating layer, and growing a zinc oxide nanowire array on a silicon substrate containing the seed layer in a growth solution; 4) coating carbon quantum dots on the surface of zinc oxide nanowire arrays; 5) Use glass through-hole technology for packaging and reserve a gas channel; lead out the top test electrode through the glass through-hole, and the through-hole electrode connects the bottom electrode and the top test electrode.
7. The preparation method according to claim 6, characterized in that: After spin coating photoresist on the surface of the silicon substrate, photolithography is performed, the rotation speed of the spin coating photoresist is 2500-3500 r / min, and the time is 1.5-2.5 min; During the photolithography process, pre-baking: 62-68°C, 2.5-3.5 min; 90-100°C, 5.5-6.5 min; exposure 105-115 s; post-baking: 62-68°C, 0.8-1.2 min; 90-100°C, 4.5-5.5 min; development 45-55 s.
8. The preparation method according to claim 6 or 7, characterized in that: The insulating layer is a silicon dioxide insulating layer; separated bottom electrodes are prepared at both ends of the insulating layer by magnetron sputtering coating, and the bottom electrodes are gold electrodes; the thickness of each bottom electrode is 85 to 95 nm.
9. The preparation method according to claim 8, characterized in that: The raw materials of the seed layer are zinc acetate, ethanolamine and anhydrous ethanol, and the molar ratio of zinc acetate to ethanolamine is 1-2:1-2; The process of spin coating the seed layer is first spin coating, second spin coating, and heating. The rotation speed of the first spin coating is 970-1030 r / min, the time is 8-12 s, the rotation speed of the second spin coating is 1500-2500 r / min, the time is 25-35 s; the heating temperature is 280-320°C, and the time is 22-27 min.
10. The preparation method according to claim 9, characterized in that: The raw materials of the growth solution are zinc nitrate, hexamethylenetetramine and water, and the molar ratio of zinc nitrate to hexamethylenetetramine is 1-1.5:1-1.5; The temperature for growing the zinc oxide nanowire array is 90-98° C., and the time is 5.5-6.5 hours.